(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Implant-supported prosthetic constructions are widely used in modern dentistry for the restoration of missing teeth. However, one of the key challenges remains ensuring their long-term durability, which directly depends on biomechanical factors. The aim of this study is to analyze the influence of load distribution, material selection, and implant positioning on clinical treatment success. It has been established that proper biomechanical planning significantly reduces the risk of complications and increases the lifespan of prosthetic restorations.